Model of Bacterial Conjugation using a Cellular Automaton and Evolutionary Computation (2015)
This thesis presents a model based on cellular automata and evolutionary computation, the purpose of the model is to abstract the behaviour and properties of a bacterial colony. In the bacterial colony, each bacterium has a set of properties and interacts with the environment and other bacteria. Depending on environment characteristics, a bacterium can carry out a set of actions (to reproduce itself, transfer plasmids, die). The obtained results show that the application of the correct use of antibiotics (the correct type of antibiotics, at the correct generation, with the correct dosis) may cause the extinction of the bacterial colony; on the opposite, the antibiotic resistance is obtained as emergent property in the bacterial colony if the mechanism of action of antibiotics is not appropriate.